2020
DOI: 10.1364/ao.382805
|View full text |Cite
|
Sign up to set email alerts
|

Effects of working pressure and power on photovoltaic and defect properties of magnetron sputtered Sb2Se3 thin-film solar cells

Abstract: Antimony selenide ( Sb 2 Se 3 ) is an emerging material with potential applications in photovoltaics, while magnetron sputtering is an important method in material growth. In this study, Sb 2 Se 3 thin films, prepared by the magnetron sputtering technique with varied working pressures and sputtering powers, were fabricated into solar cells with a structure of glass / IT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…In 2018, the DLTS was carried out on a 7.6% PCE Sb 2 Se 3 solar cell fabricated by the VTD method . Two kinds of deep acceptor defects with depth of E v +0.48 and E v +0.71 eV and one kind of deep donor defect with depth of E c -0.60 eV were observed. , The two acceptors were attributed to V Sb and Se Sb , respectively, and the donor defect was assigned to Sb Se . Similar to Sb 2 S 3 solar cells, the deep defect density in Sb 2 Se 3 was larger than 10 14 cm –3 , which could promote nonradiative recombination, resulting in the short carrier lifetime and large V OC loss .…”
Section: Emerging Chalcogenidesmentioning
confidence: 99%
“…In 2018, the DLTS was carried out on a 7.6% PCE Sb 2 Se 3 solar cell fabricated by the VTD method . Two kinds of deep acceptor defects with depth of E v +0.48 and E v +0.71 eV and one kind of deep donor defect with depth of E c -0.60 eV were observed. , The two acceptors were attributed to V Sb and Se Sb , respectively, and the donor defect was assigned to Sb Se . Similar to Sb 2 S 3 solar cells, the deep defect density in Sb 2 Se 3 was larger than 10 14 cm –3 , which could promote nonradiative recombination, resulting in the short carrier lifetime and large V OC loss .…”
Section: Emerging Chalcogenidesmentioning
confidence: 99%
“…In contrast, the defects of Sb 2 Se 3 solar cells have been comprehensively studied by several groups. 37,43,[60][61][62]65 Two kinds of deep acceptor defects (0.48 and 0.71 eV) and one kind of deep donor defect (0.62 eV) were found in undoped Sb 2 Se 3 solar cells by DLTS characterization. 60,62 Wen et al identified the 0.62 eV defect to antimony antisite (Sb Se ), 0.48 eV defect to antimony vacancy (V Sb ), and 0.71 eV defect to selenium antisite (Se Sb ).…”
mentioning
confidence: 96%
“…Since then, no additional literature reports on the defect information in Sb 2 S 3 solar cells have appeared. In contrast, the defects of Sb 2 Se 3 solar cells have been comprehensively studied by several groups. ,, , Two kinds of deep acceptor defects (0.48 and 0.71 eV) and one kind of deep donor defect (0.62 eV) were found in undoped Sb 2 Se 3 solar cells by DLTS characterization. , Wen et al identified the 0.62 eV defect to antimony antisite (Sb Se ), 0.48 eV defect to antimony vacancy (V Sb ), and 0.71 eV defect to selenium antisite (Se Sb ) . These defects generally have a density of 10 14 –10 15 cm –3 , which is 1–3 orders of magnitude greater than that of CdTe and CIGS solar cells .…”
mentioning
confidence: 99%
“…To gain further insight into the specific influence of each defect on the carrier dynamics and defect density states of the absorber, TRTA, time-resolved photoluminescence (TRPL), terahertz (THz) spectroscopy, and angular frequency-dependent capacitance were employed. 7,39,72,79,80,123 The activation energy of the dominant defects (V Sb and Se Sb ) of Sb 2 Se 3 is much larger than that of Sb 2 S 3 and kesterite materials, 78 which means that only 2.6% of the bulk defects of Sb 2 Se 3 contribute to the free carriers, leading to low free carrier density (7.7 × 10 13 cm −3 ), limited bulk conductivity, and small quasi-Fermi level splitting under illumination. The N T values of 6.9 × 10 14 cm −3 and 1 × 10 15 cm −3 were determined from space charge limited current measurement and first-principle calculation for Sb 2 Se 3 films at room temperature, respectively.…”
Section: Recombination Processes and Carrier Transport In Antimony Se...mentioning
confidence: 99%
“…In contrast, defects that introduce levels deep in the bandgap with energy much higher than k B T form deep level defects (Fig. 2(b)) 32,39,72,73 The trap states associated with deep defects usually act as detrimental traps for photogenerated carriers and act as recombination centers and dictate carrier mobility, which ultimately affects the efficiency of the device; thus, the formation of these should be avoided. Fig.…”
Section: Introductionmentioning
confidence: 99%